Management of thrombotic microangiopathy after hematopoietic cell transplantation: A position statement of ThREG (Turkish Hematology Research and Education Group). (December 2021) - Kaya, Ali Hakan; Tekgunduz, Emre
Abstract: Hematopoietic stem cell transplantation associated-thrombotic microangiopathy (TA-HCT) is one of the early complications of endothelial origin in the course of HCT. Endothelial damage to the microvascular structure and the platelet-rich microthrombi, which are formed as a result of accompanying complement activation, constitute the main pathological conditions resulting TA-TMA. Early diagnosis and management are of utmost importance to prevent multi-organ failure and death. This review summarizes the current understanding of TA-TMA regarding pathogenesis, definition, differential diagnosis, risk factors, surveillance for early diagnosis and management.